Respuesta :
Let's solve this problem step-by-step.
STEP-BY-STEP SOLUTION:
We will be using simultaneous equations to solve this problem.
Let's first establish the two equations we will be using to solve the problem.
Let number no. 1 = x
Let number no. 2 = y
Equation No. 1 -
x = y + 3
Equation No. 2 -
x + y = 27
To begin with, we will substitute the value of ( x ) from the first equation into the second equation to solve for ( y ).
Equation No. 2 -
x + y = 27
( y + 3 ) + y = 27
y + y = 27 - 3
2y = 24
y = 24 / 2
y = 12
Next we will substitute the value of ( y ) from the first equation into the first equation to solve for ( x ).
x = y + 3
x = ( 12 ) + 3
x = 15
FINAL ANSWER:
Therefore, the two numbers are 15 and 12.
Please mark as brainliest if you found this helpful! :)
Thank you and have a lovely day! <3
STEP-BY-STEP SOLUTION:
We will be using simultaneous equations to solve this problem.
Let's first establish the two equations we will be using to solve the problem.
Let number no. 1 = x
Let number no. 2 = y
Equation No. 1 -
x = y + 3
Equation No. 2 -
x + y = 27
To begin with, we will substitute the value of ( x ) from the first equation into the second equation to solve for ( y ).
Equation No. 2 -
x + y = 27
( y + 3 ) + y = 27
y + y = 27 - 3
2y = 24
y = 24 / 2
y = 12
Next we will substitute the value of ( y ) from the first equation into the first equation to solve for ( x ).
x = y + 3
x = ( 12 ) + 3
x = 15
FINAL ANSWER:
Therefore, the two numbers are 15 and 12.
Please mark as brainliest if you found this helpful! :)
Thank you and have a lovely day! <3